Atypical case of Miller-Fisher syndrome presenting with severe dysphagia and weight loss. Issue 5 (27th May 2020) - Patel, Kishan; Nussbaum, Eliezer; Sico, Jason; Merchant, Naseema
Abstract : A 71-year-old man developed dysphagia, bilateral lower extremity muscle weakness and weight loss. He was admitted to the hospital after a failed formal swallow evaluation, nearly 3 weeks after symptom onset. In addition to dysphagia and weakness, physical examination was notable for hypophonia, dysarthria, diplopia, horizontal ophthalmoparesis, ptosis, ataxia and hyporeflexia. Cerebrospinal fluid was notable for albuminocytological dissociation and serum anti-GQ1b antibody titre was elevated (1:200). A diagnosis of Miller-Fisher syndrome (MFS) was made, and the patient was treated with intravenous immunoglobulin (0.4 g/kg/day) for 5 days, which resulted in resolution of symptoms. This is an atypical case of MFS, in that the presenting symptom was progressive dysphagia rather than the ophthalmoplegia and ataxia that are normally seen in MFS. Patients who present with dysphagia should receive a thorough neurological examination, with particular attention to extraocular movements, reflexes and gait stability, to rule out MFS as a potential cause.